Potential of resveratrol in enrichment of neural progenitor-like cell induction of human stem cells from apical papilla - Anupong Songsaad (2021)
© 2020, The Author(s). Introduction: Stem cell transplantation of exogenous neural progenitor cells (NPCs) derived from mesenchymal stem cells (MSCs) has emerged as a promising approach for neurodegenerative disease. Human stem cells from apical papilla (hSCAPs) are derived from migratory neural crest stem cells and exhibit a potential of neuronal differentiation. However, their neuronal differentiation is low and unpredictable. Resveratrol has been described as a sirtuin 1 (SIRT1) activator which plays an important role in enhancing neuronal differentiation. In this study, we investigate the potential of resveratrol as an enhancer on neuronal differentiation through NPCs induction of hSCAPs. Methods: Stem cells were isolated from human apical papilla and characterized as MSCs. The cellular toxicity of resveratrol treatment to the characterized hSCAPs was investigated by MTT assay. The non-cellular toxicity concentrations of resveratrol were assessed with various pre-treatment times to select the optimal condition that highly expressed the neural progenitor gene, NES. Consequently, the optimal condition of resveratrol pre-treatment was synergistically performed with a neuronal induction medium to trigger neuronal differentiation. The differentiated cells were visualized, the genes profiling was quantified, and the percentage of neuronal differentiation was calculated. Moreover, the intracellular calcium oscillation was demonstrated. Results: The cellular toxicity of resveratrol was not observed for up to 50 μM for 12 h. Interestingly, hSCAPs pre-treated with 10 μM resveratrol for 12 h (RSV-hSCAPs) significantly expressed NES, which is determined as the optimal condition. Under neuronal induction, both of hSCAPs and RSV-hSCAPs were differentiated (d-hSCAPs and RSV-d-hSCAPs) as they exhibited neuronal-like appearances with Nissl substance staining. The highest expression of NES and SOX1 was observed in RSV-d-hSCAPs. Additionally, the percentage of neuronal differentiation of RSV-d-hSCAPs was significantly higher than d-hSCAPs for 4 times. Importantly, the neuronal-like cells exhibited slightly increasing pattern of calcium intensity. Conclusion: This study demonstrated that pre-treatment of resveratrol strongly induces neural progenitor marker gene expression which synergistically enhances neural progenitor-like cells’ induction with neuronal induction medium.